How to prevent, minimize, or extinguish nocebo effects in pain: a narrative review on mechanisms, predictors, and interventions - Manaï, Meriem (Pain Rep, 2019)
Nocebo effects, such as side effects due to negative expectations regarding the pain treatment, are a concern for health care providers and come with significant costs. This narrative review focuses on underlying mechanisms and possible factors that contribute to the susceptibility to the nocebo effect on pain and related outcomes and suggests strategies that can prevent, minimize, or extinguish nocebo effects in clinical settings. Nocebo effects are the result of psychological (eg, conditioning, verbal suggestions, and observational learning) and neurobiological (eg, cholecystokinin and dopamine regulation) mechanisms. Evidence from clinical and experimental studies lead to various recommendations and strategies to alter the nocebo effect in order to optimize pain treatments, such as providing patients with enhanced information, optimizing patient–physician communication and relationships, and offering psychoeducation on coping skills in order to manage patient expectations. The current literature from both clinical and experimental studies provides a better understanding of the nocebo effect and possible factors that modulate its strength on treatment outcomes. This allows for the development of evidence-based strategies aimed at the prevention, minimization, and treatment of the nocebo effect in pain conditions and possible other somatic disorders.